COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) FOR PAIN, HERBAL ANTI-INFLAMMATORY DRUGS - Goci, Enkelejda; Shkreli, Rezarta; Haloci, Entela; Malaj, Ledjan (European Scientific Journal, ESJ, 2013)
﻿Introduction: Many specialists in pain management view the integration of traditional treatment approaches and a wide range of complementary and alternative medicine approaches as the ideal goal of many types of pain. Pain is a subjective, complex, multidimensional and unpleasant experience. It is one of the most prevalent conditions that require medical attention. Nowadays the number of patients that are using herbal remedies and complementary and alternative medicine for treatment of pain is growing rapidly. Objectives: The aim of this investigation is to describe the concept of complementary and alternative medicine – CAM and the role of specific plants and their anti-inflammatory activity in curing inflammatory painful diseases. Conclusions: Nonsteroidal anti-inflammatory drugs and opioid analgesics are normally used to treat inflammation and pain, but they can manifest a great number of adverse effects. Therefore herbal drugs can be a potential source to replace them. Many medicinal plants, some of them indigenous, are known for their analgesic and anti-inflammatory effect, but only a few are included in the health care system after clinical research. So, it is time to give an important place to the scientific uses of natural medicinal plants and investigation of the active phytoconstituents of them. Extraction of the active principle of herbal drugs and their pharmaceutical formulation must be the main direction of industrial research.